B-21 Nanopore zeolite membrane for selective separation of ethanol-water(Session: Films/Membrane) - Tawan Sooknoi; Attawit Aryuwat (My University, 2006)
In this work, zeolite A membranes were prepared, using hydrothermal synthesis, on the surface of supports, which are the mixture of zeolite A and kaolin XRD and SEM revealed that the surface of supports were covered with polycrystalline zeolite A film having grain size of 2.5-5.0μm and have the pore size of〜0.4 nm. The zeolite A membranes were used for the separation of ethanol/water mixture in vapor phase. The experiment was carried out at 85^o℃, using 50-95% v/v ethanol as feed. The permeate was carried by Helium with flow rate 50-80 ml/min under atmospheric pressure and analyzed with on-line GC.
Keywords: Nanopore and Nanochannel Transport Studies